2D:4D indicates phimosis risk: A study on digit ratio and early foreskin development. (August 2016) - Li, Guanjian; Huo, Ying; Sun, Ke; Wang, Xiaodong; Li, Hao; Gao, Le; Ma, Bin
Abstract: Background: Many researchers have adopted 2D:4D (second to fourth finger length ratio) as a noninvasive retrospective biomarker for prenatal androgen exposure in recent years. It is thought to be related to diverse traits including behavioral phenotypes, disease susceptibility, and development of urogenital system. Objective: To examine the relationship between 2D:4D and early foreskin development. Methods: We analyzed the digit ratio and foreskin condition in 176 cases (range 0–6 years). The boys were divided into four groups according to their ages: group 1, neonates (below 28 days, n = 13); group 2, infants (1–12 months, n = 45); group 3, toddlers (1–2 years old, n = 42); group 4, preschool children (3–6 years old, n = 76). We measured the lengths of the second and fourth digits of the left and right hands. The foreskin status was classified into 4 types. Type I (phimosis), type II (partial phimosis), type III (adhesion of prepuce), type IV (normal). Results: The phimosis rate was 92.3%, 82.2%, 45.2%, and 38.7% in group 1 to group 4. In contrast, the proportion of normal foreskin increased from 0% in neonates to 13.2% in preschool children. The percentage of higher level of foreskin development shows a downward trend with the increase of digits ratio, and as the age grows, the percentage of normal foreskin cases also increases. Conclusions: These results suggest that a higher R2D:4D (right hand 2D:4D) is a risk factor for phimosis in the early human development. Age is also a significant influence factor of foreskin conditions. Additional research is required to identify pathophysiologic mechanisms and to determine clinical significance. Highlights: We assert that our results present sufficient evidence that higher 2D:4D ratio is a risk factor for phimosis in the early human development. This may be the first report about the association between Digit ratio and foreskin condition. We present a new direction and area to study the relationship between Digit ratio, hormone and the early development of human. We call for further research to explore the physiological and biochemical mechanism about the hormones responsible for the separation of the glans-prepuce.